Analysis And Design Of A Website-Based Information System For Educational Development Contribution Payments Smks Yapenap - Ahmad Faiz Muqtasid (LPPM & Fakultas Teknologi Informasi UNSAP, 2026)
SMKS Yapenap still manages tuition fee payments manually using spreadsheets, which increases the risk of recording errors and slows down report preparation. This study aims to analyze and design a website-based tuition fee payment information system to improve operational efficiency and data accuracy. The methodology used is Rapid Application Development (RAD) with Unified Modeling Language (UML) modeling. System requirements analysis is also supported by the PIECES framework to evaluate performance and service aspects. The results of the study are a system design with a centralized database that enables real-time data management. An automatic validation feature is designed to minimize human error and speed up the transaction process. In addition, this portal provides transparency for parents in monitoring payment status independently. In conclusion, the RAD method is effective in producing a professional and accountable financial management solution for SMKS Yapenap.